Polarization optical-histochemical characterization and supramolecular structure of carbohydrate fibrils - Csóka, Levente; Appel, Thomas R.; Eitner, Annett; Jirikowski, Gustav; Makovitzky, József (Acta histochemica, 2013)
Topo-optical staining reactions were used to investigate the structures of bacterial cellulose, insect chitosan and alginic acid from brown algae. Polysaccharide complexes, glycosaminoglycans and sulfate groups were presented and demonstrated selectively. Chitosan and alginic acid are structurally similar to glycosaminoglycans (GAGs), which are constituents of human amyloid fibrils. The staining sequences shown can be used as reliable methods for histochemistry with light and polarization microscopy. They will help to clarify the complex protein-polysaccharide structure of amyloid fibrils.